Regulation of p53 expression by thymidylate synthase - Ju, Jingfang (The National Academy of Sciences, 1999)
Previous studies showed that thymidylate synthase (TS), as an RNA binding protein, regulates its own synthesis by impairing the translation of TS mRNA. In this report, we present evidence that p53 expression is affected in a similar manner by TS. For these studies, we used a TS-depleted human colon cancer HCT-C cell that had been transfected with either the human TS cDNA or the Escherichia coli TS gene. The level of p53 protein in transfected cells overexpressing human TS was significantly reduced when compared with its corresponding parent HCT-C cells. This suppression of p53 expression was the direct result of decreased translational efficiency of p53 mRNA. Similar results were obtained upon transfection of HCT-C cells with pcDNA 3.1 (+) containing the E. coli TS gene. These findings provide evidence that TS, from diverse species, specifically regulates p53 expression at the translational level. In addition, TS-overexpressing cells with suppressed levels of p53 are significantly impaired in their ability to arrest in G(1) phase in response to exposure to a DNA-damaging agent such as γ-irradiation. These studies provide support for the in vivo biological relevance of the interaction between TS and p53 mRNA and identify a molecular pathway for controlling p53 expression.